Comparative Study of Statistical Distributions in Electromigration-Induced Failures of Al/Cu Thin-Film Interconnects - M. I. Loupis; J. N. Avaritsiotis; G. D. Tziallas (Active and Passive Electronic Components)
In electromigration failure studies, it is in general assumed that electromigration-induced failures may be adequately modelled by a log-normal distribution. Further to this, it has been argued that a lognormal distribution of failure times is indicative of electromigration mechanisms. We have combined post processing of existing life-data from Al/Cu + TiW bilayer interconnects with our own results from Al/Cu interconnects to show that the Log Extreme Value distribution is an equally good statistical model for electromigration failures, even in cases where grain size exceeds the linewidth. The significance of such a modelling is particularly apparent in electromigration failure rate prediction.